DOES INSULIN RESISTANCE IMPAIR THE VIROLOGICAL RESPONSE TO PEGINTERFERON/RIBAVIRIN IN CHRONIC HEPATITIS C GENOTYPE 3 PATIENTS? - Laurito, Marcela Pezzoto; Silva, Giovanni Faria; Cheinquer, Hugo; Sharma, Rajani; Verna, Elizabeth; Parise, Edison Roberto (Instituto Brasileiro de Estudos e Pesquisas de Gastroenterologia e Outras Especialidades - IBEPEGE., 2018)
ABSTRACTBACKGROUND:Insulin resistance and diabetes mellitus are common extrahepatic manifestations of chronic hepatitis C (HCV). Insulin resistance assessed by HOMA-IR is associated with low rates of sustained virological response, especially in HCV genotype 1 positive patients treated with peginterferon/ribavirin. The effect of insulin resistance on sustained virologic response in HCV genotype 3 positive patients who were treated with peginterferon/ribavirin still remains unclear.OBJECTIVE:To evaluate the impact of insulin resistance on sustained virological response in HCV genotype 3 patients treated with peginterferon/ribavirin.METHODS:A retrospective multicenter study was performed to evaluate the impact of insulin resistance on sustained virological response in non-diabetic HCV genotype 3 positive patients treated with peginterferon and ribavirin. A total of 200 HCV genotype 3 positive patients were enrolled in the study. All patients were non-diabetic. Each patient had a HOMA-IR value measured before the initiation of HCV treatment with peginterferon/ribavirin. The treatment duration was at least 24 weeks. The HOMA-IR cut-off was defined in the study as ≥2.5 due to the coefficient of correlation with sustained virological response of 0.202 (P=0.004).RESULTS:Univariate analysis showed that age, aspartate aminotransferase, platelets, stage of fibrosis and HOMA-IR were predictors of sustained virological response. However multivariate analysis showed advanced fibrosis [OR=2.01 (95%CI: 0.986-4.119) P=0.05] and age [OR=1.06 (95%CI: 1.022-1.110) P=0.002] as negative predictors of sustained virological response.CONCLUSION:In this retrospective multicenter study of non-diabetic HCV genotype 3 positive patients, insulin resistance was not associated with the sustained virological response in patients who were treated with peginterferon/ribavirin.

RESUMOCONTEXTO:A resistência insulínica e o diabetes mellitus são frequentes manifestações extra-hepáticas da hepatite C crônica. A resistência insulínica medida pelo HOMA-IR está associada a uma baixa taxa de resposta virológica sustentada, principalmente em pacientes portadores de hepatite C crônica genótipo 1 tratados com peginterferon/ribavirina. Em relação aos pacientes portadores de hepatite C crônica genótipo 3 tratados com peginterferon/ribavirina, a influência da resistência insulínica na resposta virológica sustentada ainda não está esclarecida.OBJETIVO:Avaliar a influência da resistência insulínica na resposta virológica sustentada em pacientes portadores de hepatite C crônica genótipo 3.MÉTODOS:Estudo multicêntrico retrospectivo foi realizado para avaliar a influência da resistência insulínica na resposta virológica sustentada em pacientes não-diabéticos portadores de hepatite C crônica genótipo 3 tratados com peginterferon/ribavirina. Um total de 200 pacientes portadores de hepatite C crônica genótipo 3 foi incluído no estudo. Todos os pacientes eram não diabéticos e apresentavam medida de HOMA-IR antes do início do tratamento da hepatite C crônica com peginterferon/ribavirina. A duração do tratamento foi de pelo menos 24 semanas. O cut-off de HOMA-IR foi definido para este estudo como ≥2,5 devido ao coeficiente de correlação com a resposta virológica sustentada de 0,202 (P=0,004).RESULTADOS:Na análise univariada, idade, aspartato aminotransferase, plaquetas, grau de fibrose e HOMA-IR foram preditores de resposta virológica sustentada. No entanto, na análise multivariada, apenas fibrose avançada [OR=2,01 (95%IC: 0,986-4,119) P=0,05] e idade [OR=1,06 (95%IC: 1,022-1,110) P=0,002] estavam relacionados como preditores negativo de resposta virológica sustentada.CONCLUSÃO:Neste estudo multicêntrico, retrospectivo, em pacientes não diabéticos portadores de hepatite C genótipo 3, a resistência insulínica não estava associada à resposta virológica sustentada em pacientes tratados com peginterferon/ribavirina.
Resistência insulínica interfere na resposta virológica sustentada em pacientes portadores de hepatite C crônica genótipo 3 tratados com peginterferon/ribavirina?
Keywords: Chronic hepatitis C; Genotype; Insulin resistance; Ribavirin; Antiviral agents; Hepatite C crônica; Genótipo; Resistência à insulina; Ribavirina; Antivirais